Notes on breeding behaviour, ecology, taxonomy and vocalisations of Satanic Nightjar Eurostopodus diabolicus in Central Sulawesi - Ding Li Yong; J. Berton C Harris; Pamela C Rasmussen; Richard Noske; Dadang Dwi Putra; William Rutherford; Idris Tinulele; Dewi M Prawiradilaga (KUKILA, 2012)
The Satanic Nightjar Eurostopodus diabolicus, rediscovered in 1996, is a hitherto poorly known nocturnal bird endemic to Sulawesi’s hill and montane forests with only two documented nest records to date. Here, we describe two further nest records from the Anaso track in Lore Lindu National Park (LLNP), Central Sulawesi, as well as threat behaviour and vocalisations of the species. We also briefly comment on its taxonomy based on our evaluation of the holotype. Both nests were found well-concealed on the ground in forest clearings with dense ferns and moss growth and both contained single chicks. The clutch size for the species is one. The incubation period is unknown, but probably similar to other Australasian Eurostopodus nightjars. We estimate the time to fledge to be about 30–45 days. Our record of an actively vocalizing individual at 2,300m asl extends the known upper elevation limit of the species. Our documentation of diagnosable plumage and vocal differences between birds in North and Central Sulawesi suggests that the species is not monotypic. Although our observations show that Satanic Nightjar is able to utilise forest clearings and has a fairly wide elevational range, it appears to be locally common only around Anaso track and we failed to find it despite intensive surveys in other parts of LLNP. Further surveys would be needed to clarify its distribution and status in other parts of Sulawesi.